Quantitative risk assessment: methodology and application in an automaker body-in-white production line project - de França Poggi, Thiago; Oliveira Duarte, Heitor; Santos Campos de Siqueira, Paulo Gabriel; Dayvson Marques Ferreira, Adriano (Revista Gestão da Produção Operações e Sistemas, 2024)
Purpose: the presented research aims to present a new methodology called quantitative risk assessment for body-in-white projects, to predict the likely time to deliver the project and the project total cost, through its application in a real project in an automaker in Brazil. Theoretical framework: this paper uses risk analysis methods (e.g., program evaluation and review technique, preliminary hazard analysis, gaussian curve, Monte Carlo simulation) and project management tools for problem characterization (e.g, project requirements, assumptions, work breakdown structure). Methodology/Approach: the methodology presented in this paper follows a sequence of methods that, firstly, (i) identifies the hazards; then, (ii) evaluates the probability of the risks applied in each task of the project; (iii) evaluates its consequences and impact on costs of the project; and, at last, (iv) quantifies the risks to predict a spectrum of the probability of the project’s final cost to estimate an emergency reserve and categorize the level of the risk to report the stakeholders. Findings: this paper shows that, given the 66 identified hazards, there is a 37% probability of the project to extend for more than 200 days, and the project has been categorized as high risk (i.e., more than 20% probability of the extra cost being above 20% of the project’s estimated cost). Research, practical & social implications: The study allows organizations to predict likely risks impacts on project schedule and costs through risk assessments and to use this information as input to project risk management. Originality/ Value: The value of the study is due to its methodology originality of risk assessment application on automakers’ body-in-white projects.